2005
DOI: 10.1194/jlr.d500008-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

A simple and rapid method to measure cholesterol binding to P450s and other proteins

Abstract: Cholesterol plays an important role in cellular function and membrane compartmentalization and is involved in the interaction with more than a dozen of different proteins. Using three cholesterol-metabolizing cytochrome P450s (P450s 7A1, 46A1, and 11A1), we have developed a rapid and simple assay for measurements of nanomolar to micromolar cholesterol affinities. In this assay, the P450 is incubated with a fixed amount of radiolabeled cholesterol and varying concentrations of cold cholesterol followed by separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…This result confirmed that Tween 20 is essential for the high catalytic activity under these experimental conditions, as reported previously (29,30). Cholesterol binding to Tween 20 and HP␤CD has been reported with K d values of 2.5 and 1.5 mM, respectively (29), which were used here. All models used to fit the data in this report include these two equilibria (i.e.…”
Section: Cholesterol 7␣-hydroxylation Activity Of P450 7a1-thesupporting
confidence: 68%
“…This result confirmed that Tween 20 is essential for the high catalytic activity under these experimental conditions, as reported previously (29,30). Cholesterol binding to Tween 20 and HP␤CD has been reported with K d values of 2.5 and 1.5 mM, respectively (29), which were used here. All models used to fit the data in this report include these two equilibria (i.e.…”
Section: Cholesterol 7␣-hydroxylation Activity Of P450 7a1-thesupporting
confidence: 68%
“…The fi nal concentration of HP ␤ CD in each reaction mixture was 3.1 mM. The binding constant ( K d ) of cholesterol with HP ␤ CD is reported to be 1.05 mM ( 31 ), and the same value was used in calculations for 7-dehydrocholesterol and desmosterol, in that the calculated logarithms of the octanol-water partition coeffi cients (cLogP values) for cholesterol, 7-dehydrocholesterol, and desmosterol are of the same order of magnitude, i.e., 6.52, 6.30, and 6.04, respectively (ChemDraw, Cambridgesoft, Cambridge, MA). The concentration of free substrate was calculated using the cholesterol K d value of 1.05 mM and a simple binding model (i.e., substrate + HP ␤ CD substrate-HP ␤ CD ).…”
Section: Discussionmentioning
confidence: 99%
“…The P450 concentration in these experiments was 5 M. The apparent dissociation constants of the enzyme-substrate complex (K d ) were calculated in Prism version 6 (GraphPad Software, La Jolla, CA) by fitting the data for the substrate-induced absorbance changes in the difference spectra ⌬(A 390 Ϫ A 420 ) versus substrate concentration to a onesite total binding equation (binding-saturation). Correction was made for the equilibrium with HPCD by fitting to two equations, the equilibrium expressions for binding of the sterols to both the P450 and HPCD (34,35), in the program DynaFit (36), with the assumption that the K d value for cholesterol is similar to those of the sterols examined here.…”
Section: Methodsmentioning
confidence: 99%